2021
DOI: 10.1111/jcmm.16459
|View full text |Cite
|
Sign up to set email alerts
|

Osthole enhances the immunosuppressive effects of bone marrow‐derived mesenchymal stem cells by promoting the Fas/FasL system

Abstract: Thanks to the advantages of easy harvesting and escape from immune rejection, autologous bone marrow‐derived mesenchymal stem cells (BMSCs) are promising candidates for immunosuppressive therapy against inflammation and autoimmune diseases. However, the therapy is still challenging because the immunomodulatory properties of BMSCs are always impaired by immunopathogenesis in patients. Because of its reliable and extensive biological activities, osthole has received increased clinical attention. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…One hypothesis suggestes that the upregulation of protein and mRNA expression level of autophagy-associated genes, Beclin1, and LC3 may be the cause [107]. Yang et al found osthole could restore the immunosuppressive ability of osteoporotic BMMSCs and enhance the immunosuppressive effects by promoting the Fas/FasL system [108]. Osthole can also promote bone strength and enhance fracture healing through the activation of BMP2 signaling in chondrocytes [109].…”
Section: Osteogenic Activitymentioning
confidence: 99%
“…One hypothesis suggestes that the upregulation of protein and mRNA expression level of autophagy-associated genes, Beclin1, and LC3 may be the cause [107]. Yang et al found osthole could restore the immunosuppressive ability of osteoporotic BMMSCs and enhance the immunosuppressive effects by promoting the Fas/FasL system [108]. Osthole can also promote bone strength and enhance fracture healing through the activation of BMP2 signaling in chondrocytes [109].…”
Section: Osteogenic Activitymentioning
confidence: 99%
“…Recently, the immunosuppressive effect of MSCs is the hotspot for MSC treatment. Several studies have confirmed that the Fas/FasL system is important for T­cell apoptosis in inflammatory and immune diseases [ 28 30 ], and enhancement of Fas/FasL expression is a promising strategy to improve MSC cytotherapy at the molecular level [ 31 ]. In our study, we found that SCC could increase the expression of APO-1 at both the transcriptional level of mRNA and protein level in BM MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that knub recurrence may be hardly interrelated to the mechanism of immune escape. FasL gene is an important member of the knub necrosis family and is an important factor in the occurrence of immune escape in bladder carcinoma [ 15 ]. The taller level of NMP22 in sufferers with bladder carcinoma before surgery may indicate that the taller the conveying of FasL gene, the more prone to immune escape.…”
Section: Discussionmentioning
confidence: 99%